Bovine Tuberculosis, A Zoonotic Disease - Tarmudji .; Supar . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
Bovine tuberculosis is caused by the infection of Mycobacterium tuberculosis var. bovis (M. bovis). This species is one of Mycobacterium tuberculosis complex, can infect wide range of hosts: cattle and other domesticated animals, wild mammals and humans (zoonotic). M. bovis bacterium from infected hosts can be transmitted to other susceptible animals and humans through respiratory excretes and secretion materials. Humans can be infected with M. bovis by ingested M. bovis contaminated animal products, unpasteurised milk from tuberculosis cows or through respiratory route of contaminated aerosol. Bovine tuberculosis at the first stage does not show any clinical sign but as the disease progress in the next stage which may take several months or years, clinical signs may arise, suh as: fluctuative body temperature, anorexia, lost body weight, coughing, oedema of lymph nodes, increased respiratory frequencies. Pathological lesion of bovine tuberculosis is characterised by the formation of granulomas (tubercles), in which bacterial cells have been localised, most in lymph nodes and pulmonum, but can occur in other organs. The granulomas usually arise in small nodules or tubercles appear yellowish either caseus, caseo-calcareus or calcified. In Indonesia, bovine tuberculosis occurred in dairy cattle since 1905 through the imported dairy cows from Holland and Australian. It was unfortunate that until recently, there were not many research and surveilances of bovine tuberculosis conducted in this country, so the distribution of bovine tuberculosis is unknown. Early serological diagnosis can be done on live cattle by means of tuberculin tests under field conditions. Confirmation can be done by isolation and identification of excreted and secreted samples from the slaughter house. Antibiotic treatment and vaccination were uneffective, therefore the effective control of bovine tuberculosis is suggested by tuberculin tests and by slaughtering the selected positive reactors.   Key words: Bovine tuberculosis, Mycobacterium bovis, zoonotic disease